Religious Values in the Sonaf Structure of the Meko Nipani Tribe and Their Relevance to the Theological Inculturation of the Christian Faith in Sacato, East Timor - Senda, Siprianus Soleman; Vianey, Watu Yohanes; Subani, Yohanes; Naif, Oktovianus; Undat, Rikardus; Costa, Francesco da; Silva, Augusto Almeida da; Lasi, Bartolomeu dos Santos; Turkel, Ajito Abel Anjos (AL-ADYAN, 2026)
The structure of the Sonaf traditional house of the Meko Nipani tribe in Sacato, Oecusse, East Timor represents a religious value system that regulates the relationship between humans, ancestors, nature, and the Divine. This traditional house not only functions as a residence but also as a sacred space containing cosmological symbols and communal living ethics rooted in the belief in Uis Neno and the principle of the unity of Nekaf Mese Ansaof Mese. This research stems from the reality of the Sacato community, which is predominantly Christian but still faces challenges in integrating church faith with the structure of local cultural and religious values. In this context, this research examines how the religious values embodied in the structure of the Sonaf traditional house can be interpreted as an opportunity for the contextual inculturation of the Christian faith. The method employed involves a study of anthropological and theological literature linked to inculturative reflection on the symbols, spatial functions, and religious meaning of the Meko Nipani traditional house. The findings indicate that the Sonaf structure embodies religious principles such as community unity, respect for ancestors, the sacredness of living space, and orientation toward the Divine—all of which are theologically aligned with Christian values. These findings confirm that the inculturation of the Christian faith does not have to conflict with local traditions but can instead flourish through creative dialogue with the religious symbols and values of traditional houses. Thus, traditional houses can be understood as a medium for Christian inculturation, enriching the faith life of the Sacato community in a contextually relevant and culturally rooted manner.